Use of homoeopathy In animals - A review - Dua, K; Trehan, P K (The Indian Journal of Animal Sciences, 2005)
Homeopathy is practiced in human beings and animals in various parts of the world. There is a very good relationship between increased use of homoeopathy and increased animal welfare problems. Homoeopathic remedies are used to treat infectious diseases, chronic diseases and prevent diseases of animals. The lack of speech in animals, interspecies differences, lack of family history and proving of drugs in animals make veterinary homoeopathy more complex than usual veterinary consultation. The practice of homoeopathy relies heavily on principles elucidated a century or more ago, which have not been studied to any great degree for most remiedies by modern scientific methods. The homoeopathic law of similars is fundamentally the procedures by which the treatment of disease using a substance which has the power to produce similar symptoms in a healthy body. In homoeopathic medicines potentization is carried out successively by dilution and sucession. Once a remedies diluted beyond 24x or 12C potencies they are diluted beyond Avagadro's Number (6.23 x 1O¯²³) which theriotically indicates that no definite effectiveness with homoeopathic remedies beyond this dilution. Both laboratory and clinical results over a period of time have demonstrated definite effectiveness with homoeopathic remedies beyond this dilution. Mechanisms have been postulated but have not been well studied. In acute cases lower potencies can be given frequently whereas in chronic cases higher potencies may be administered less frequently.